2019
DOI: 10.2134/jeq2018.09.0332
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Herd‐Scale Methane Emissions from Cattle in a Feedlot Using Eddy Covariance Measurements and the Carbon Dioxide Tracer Method

Abstract: Measurements of methane (CH4) emissions from ruminants could provide invaluable data to reduce uncertainties in the global CH4 budget and to evaluate mitigation strategies to lower greenhouse gas emissions. The main objective of this study was to evaluate a new CO2 tracer (CO2T) approach that combined CH4 and CO2 atmospheric concentrations with eddy covariance (EC) CO2 flux measurements to estimate CH4 emissions from cattle in a feedlot. A closed‐path EC system was used to measure CH4 and CO2 fluxes from a fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…From this perspective, our simple seasonal scaling exercise may underestimate or overestimate methane emissions from bison grazing systems for multiple reasons that must be kept in mind when interpreting results. Methane emissions from cattle have been observed to be on the order of 10 %-17 % higher in summer than winter (Todd et al, 2014;Prajapati andSantos, 2018, 2019) such that our wintertime methane flux observations may be lower than what full annual measurements would yield. Our observations were similar to wintertime measurements of beef cattle in a feedlot, on the order of 75 g CH 4 per animal d −1 (Prajapati and Santos, 2019), which to a first order suggests that bison and cattle grazing systems may have similar methane efflux.…”
Section: Bison Methane Flux Observations In the Context Of Other Grazmentioning
confidence: 66%
See 3 more Smart Citations
“…From this perspective, our simple seasonal scaling exercise may underestimate or overestimate methane emissions from bison grazing systems for multiple reasons that must be kept in mind when interpreting results. Methane emissions from cattle have been observed to be on the order of 10 %-17 % higher in summer than winter (Todd et al, 2014;Prajapati andSantos, 2018, 2019) such that our wintertime methane flux observations may be lower than what full annual measurements would yield. Our observations were similar to wintertime measurements of beef cattle in a feedlot, on the order of 75 g CH 4 per animal d −1 (Prajapati and Santos, 2019), which to a first order suggests that bison and cattle grazing systems may have similar methane efflux.…”
Section: Bison Methane Flux Observations In the Context Of Other Grazmentioning
confidence: 66%
“…Footprint models of the type used here have been found to accurately estimate point sources of trace gas flux (Heidbach et al, 2017;Dumortier et al, 2019), but it is important to note that footprint modeling techniques play a large role in the spatial attribution of observed fluxes of ruminant trace gas flux (Felber et al, 2015). Prajapati and Santos (2018), for instance, found that an analytical model (Kormann and Meixner, 2001) predicted flux footprint areas 5 to 6 times larger than did an approximation of a Lagrangian dispersion model (Kljun et al, 2002) did such that footprint model uncertainty is a major source of uncertainty for measuring methane flux from multiple point sources as we also find here. Regarding the footprint model it is also important to note that emitted gas is warmer than the surrounding environment in our case.…”
Section: Bison Spatial Distribution and Measurement Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…With this method, technologies such as optimal sensors are employed to assess how gas and energy are exchanged, as well as the momentum between the different ecosystems [50]. However, to effectively use the method, knowledge of the total number of animals and their locations within the footprint is important.…”
Section: Eddy Covariance (Ec) Techniquementioning
confidence: 99%